2011
DOI: 10.4049/jimmunol.1003471
|View full text |Cite
|
Sign up to set email alerts
|

Docking of Lytic Granules at the Immunological Synapse in Human CTL Requires Vti1b-Dependent Pairing with CD3 Endosomes

Abstract: Lytic granule (LG)-mediated apoptosis is the main mechanism by which CTL kill virus-infected and tumorigenic target cells. CTL form a tight junction with the target cells, which is called the immunological synapse (IS). To avoid unwanted killing of neighboring cells, exocytosis of lytic granules (LG) is tightly controlled and restricted to the IS. In this study, we show that in activated human primary CD8+ T cells, docking of LG at the IS requires tethering LG with CD3-containing endosomes (CD3-endo). Combinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 63 publications
(83 reference statements)
4
65
0
Order By: Relevance
“…The multifocal nature of the nascent CS suggests that granules may be released at many different locations at the synaptic interface, which are most likely associated with the foci containing aggregated cognate pMHC and adhesion molecules. This is consistent with the most recent observation that a fraction of cytolytic granules are paired with TCR-containing endosomes and that the pairing is mediated by SNARE protein Vti1b (99). Pairs of endosomes are enriched at the CTL contact surface suggesting that the pairing may facilitate granule transport to the synaptic interface.…”
Section: The Role Of the Cytolytic Synapsesupporting
confidence: 93%
“…The multifocal nature of the nascent CS suggests that granules may be released at many different locations at the synaptic interface, which are most likely associated with the foci containing aggregated cognate pMHC and adhesion molecules. This is consistent with the most recent observation that a fraction of cytolytic granules are paired with TCR-containing endosomes and that the pairing is mediated by SNARE protein Vti1b (99). Pairs of endosomes are enriched at the CTL contact surface suggesting that the pairing may facilitate granule transport to the synaptic interface.…”
Section: The Role Of the Cytolytic Synapsesupporting
confidence: 93%
“…Lysates from matched Panx1 wild type and KO tissues were generated from animals from Genentech (Qu et al, 2011) and KOMP (Qiu et al, 2011; Santiago et al, 2011). Methods for the preparation of tissues lysates and Western blots for the KOMP KO are described in (Santiago et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This analysis showed that lytic granules and MTOC dynamics were heterogeneous and clearly not synchronized in the various cells analyzed. The dynamics of lytic granules and MTOC was recently studied using TIRFM in human CTL (18) and mouse NK cells (19) stimulated by immobilized anti-CD3 or anti-NKp30 and anti-CD18, respectively. In human CTLs, it was found that the MTOC did not enter in the TIRF plane (18); conversely, in mouse NK cells, it was found that MTOC appeared in the TIRF plane and lytic granules mostly associated with MTOC (19).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of lytic granules and MTOC was recently studied using TIRFM in human CTL (18) and mouse NK cells (19) stimulated by immobilized anti-CD3 or anti-NKp30 and anti-CD18, respectively. In human CTLs, it was found that the MTOC did not enter in the TIRF plane (18); conversely, in mouse NK cells, it was found that MTOC appeared in the TIRF plane and lytic granules mostly associated with MTOC (19). In line with the latter observation, superresolution microscopy analysis of the NK secretory domain showed that MTOC polarizes toward the granule penetrable synaptic areas of the actin meshwork (20).…”
Section: Discussionmentioning
confidence: 99%